THE ROLE OF PERSONAL CHARACTER AND TRAITS IN CAREER CHOICE - Davronjon M. Muminov (Bright Mind Publishing, 2025)
This article explores the psychological relationship between adolescents' character accentuations and their professional preferences. Based on a study involving 142 students aged 14–16, the research utilizes L. Shmishek's Character Accentuation Test to identify the dominant personality features among participants and relates these findings to their indicated career interests. The results demonstrate a significant correlation between specific character types and selected career fields, supporting the hypothesis that personality traits play a key role in vocational orientation. The article also proposes practical recommendations for career counselors, school psychologists, and parents.
Keywords: career choice, character accentuation, Shmishek test, personality, adolescence, professional orientation.